The disruptive power of cloud gaming platforms within the console videogame industry - Ferreira, Sofia de Castro Mendes (2020)
Over the years, the console video game industry has undergone several disruptive changes, which are reflected in continued growth. Cloud gaming, the combination of the concepts of cloud computing and online gaming, provides the entire game experience for users from a data centre. This research aims to study the disruptive power, within the console video game industry, the emergence of a hardware-agnostic cloud gaming. Firstly, the impact of cloud gaming on the console video game industry in the short term is analysed considering three dimensions: changes in the business model, the content monetization strategies and the penetration rate of this technology. The impact on the business model is reflected in the emergence of new stakeholders and the reversal of cash flows. Due to these changes, charging mechanisms have to be adapted, subscription plans are the dominant strategy. Although the estimated penetration rate is low, it is expected to grow significantly in the coming years. Subsequently, how the industry under review will look like in the long run, after absorbing the full impact of the disruptor is studied. To this end, three consolidated future scenarios were created, taking into account the behaviour of the industry primary stakeholders and its influencers (technology and business model). In the most likely scenario, cloud gaming services gradually thrive, becoming the fourth industry segment. Due to network effects, this industry is expected to have an oligopolistic structure. This scenario requires adaptations from all stakeholders, which is studied throughout this thesis, highlighting its managerial relevance.